Tracking active groundwater microbes with D2O labelling to understand their ecosystem function. (15th December 2017) - Taubert, Martin; Stöckel, Stephan; Geesink, Patricia; Girnus, Sophie; Jehmlich, Nico; von Bergen, Martin; Rösch, Petra; Popp, Jürgen; Küsel, Kirsten
Summary: Microbial activity is key in understanding the contribution of microbial communities to ecosystem functions. Metabolic labelling with heavy water (D2 O) leads to the formation of carbon–deuterium bonds in active microorganisms. We illustrated how D2 O labelling allows monitoring of metabolic activity combined with a functional characterization of active populations in complex microbial communities. First, we demonstrated by single cell Raman microspectroscopy that all measured bacterial cells from groundwater isolates growing in complex medium with D2 O were labelled. Next, we conducted a labelling approach with the total groundwater microbiome in D2 O amended microcosms. Deuterium was incorporated in most measured cells, indicating metabolic activity in the oligotrophic groundwater. Moreover, we spiked the groundwater microbiome with organic model compounds. We discovered that heterotrophs assimilating veratric acid, a lignin derivative, showed higher labelling than heterotrophs assimilating methylamine, a degradation product of biomass. This difference can be explained by dilution of the deuterium through hydrogen from the organic compounds. Metaproteomics identified Sphingomonadaceae and Microbacteriaceae as key players in veratric acid degradation, and the metabolic pathways employed. Methylamine, in contrast, stimulated various proteobacterial genera. We propose this combined approach of Raman microspectroscopy and metaproteomics for elucidating the complex metabolic response of microbial populations to different stimuli.